Understanding artificial intelligence : fundamentals and applications - Liu, Albert Chun-Chen; Law, Oscar Ming Kin; Law, Iain (Hoboken, New Jersey : Wiley-IEEE Press, 2022)
"This is an introductory book for professionals and undergraduate students without any background in artificial intelligence. The book describes how the new artificial intelligence technology, neural network, totally changes our everyday life. It first describes the neural network development history and introduces the classical neural network -- convolutional neural network architecture. After that, it covers the artificial development in six different areas; healthcare, finance, retail, manufacturing, agriculture, and smart city. This book targets students with different backgrounds, such as, business, humanity, arts, science and engineering, allowing them to understand the artificial intelligent general applications and how this impacts on their future."--
1 Introduction 1 -- 1.1 Overview 1 -- 1.2 Development History 3 -- 1.3 Neural Network Model 6 -- 1.4 Popular Neural Network 7 -- 1.4.1 Convolutional Neural Network 7 -- 1.4.2 Recurrent Neural Network 8 -- 1.4.3 Reinforcement Learning 9 -- 1.5 Neural Network Classification 9 -- 1.5.1 Supervised learning 10 -- 1.5.2 Semi-supervised learning 10 -- 1.5.3 Unsupervised learning 11 -- 1.6 Neural Network Operation 11 -- 1.6.1 Training 11 -- 1.6.2 Inference 12 -- 1.7 Application Development 12 -- 1.7.1 Business Planning 14 -- 1.7.2 Network Design 14 -- 1.7.3 Data Engineering 14 -- 1.7.4 System Integration 15 -- Exercise 16 -- 2 Neural Network 17 -- 2.1 Convolutional Layer 19 -- 2.2 Activation Layer 20 -- 2.3 Pooling Layer 21 -- 2.4 Batch Normalization 22 -- 2.5 Dropout Layer 22 -- 2.6 Fully Connected Layer 23 -- Exercise 24 -- 3 Machine Vision 25 -- 3.1 Object Recognition 25 -- 3.2 Feature Matching 27 -- 3.3 Facial Recognition 28 -- 3.4 Gesture Recognition 30 -- 3.5 Machine Vision Applications 31 -- 3.5.1 Medical Diagnosis 31 -- 3.5.2 Retail Applications 32 -- 3.5.3 Airport Security 33 -- Exercise 34 -- 4 Natural Language Processing 35 -- 4.1 Neural Network Model 36 -- 4.1.1 Convolutional Neural Network 36 -- 4.1.2 Recurrent Neural Network 37 -- 4.1.2.1 Long Short-Term Memory Network 38 -- 4.1.3 Recursive Neural Network 39 -- 4.1.4 Reinforcement Learning 40 -- 4.2 Natural Language Processing Applications 41 -- 4.2.1 Virtual Assistant 41 -- 4.2.2 Language Translation 42 -- 4.2.3 Machine Transcription 43 -- Exercise 45 -- 5 Autonomous Vehicle 46 -- 5.1 Levels of Driving Automation 46 -- 5.2 Autonomous Technology 48 -- 5.2.1 Computer Vision 48 -- 5.2.2 Sensor Fusion 49 -- 5.2.3 Localization 51 -- 5.2.4 Path Planning 52 -- 5.2.5 Drive Control 52 -- 5.3 Communication Strategies 53 -- 5.3.1 Vehicle-to-Vehicle Communication 54 -- 5.3.2 Vehicle-to-Infrastructure Communication 54 -- 5.3.3 Vehicle-to-Pedestrian Communication 55 -- 5.4 Law Legislation 56 -- 5.4.1 Human Behavior 57 -- 5.4.2 Lability 57 -- 5.4.3 Regulation 58 -- 5.5 Future Challenges 58 -- 5.5.1 Road Rules Variation 58 -- 5.5.2 Unified Communication Protocol 58 -- 5.5.3 Safety Standard and Guideline 59 -- 5.5.4 Weather/Disaster 59 -- Exercise 60 -- 6 Drone 61 -- 6.1 Drone Design 61 -- 6.2 Drone Structure 62 -- 6.2.1 Camera 63 -- 6.2.2 Gyro Stabilization 63 -- 6.2.3 Collision Avoidance 64 -- 6.2.4 Global Positioning System 64 -- 6.2.5 Sensors 64 -- 6.3 Drone Regulation 65 -- 6.3.1 Recreational Rules 65 -- 6.3.2 Commercial Rules 66 -- 6.4 Applications 66 -- 6.4.1 Infrastructure Inspection 66 -- 6.4.2 Civil Construction 67 -- 6.4.3 Agriculture 68 -- 6.4.4 Emergency Rescue 69 -- Exercise 70 -- 7 Healthcare 71 -- 7.1 Telemedicine 71 -- 7.2 Medical Diagnosis 72 -- 7.3 Medical Imaging 73 -- 7.4 Smart Medical Device 74 -- 7.5 Electronic Health Record 76 -- 7.6 Medical Billing 77 -- 7.7 Drug Development 78 -- 7.8 Clinical Trial 79 -- 7.9 Medical Robotics 80 -- 7.10 Elderly Care 81 -- 7.11 Future Challenges 82 -- Exercise 84 -- 8 Finance 85 -- 8.1 Fraud Prevention 85 -- 8.2 Financial Forecast 88 -- 8.3 Stock Trading 89 -- 8.4 Banking 91 -- 8.5 Accounting 94 -- 8.6 Insurance 95 -- Exercise 96 -- 9 Retail 97 -- 9.1 E-Commerce 98 -- 9.2 Virtual Shopping 100 -- 9.3 Product Promotion 102 -- 9.4 Store Management 103 -- 9.5 Warehouse Management 104 -- 9.6 Inventory Management 106 -- 9.7 Supply Chain 108 -- Exercise 110 -- 10 Manufacturing 111 -- 10.1 Defect Detection 112 -- 10.2 Quality Assurance 113 -- 10.3 Production Integration 114 -- 10.4 Generative Design 115 -- 10.5 Predictive Maintenance 117 -- 10.6 Environment Sustainability 118 -- 10.7 Manufacturing Optimization 119 -- Exercise 121 -- 11 Agriculture 122 -- 11.1 Crop and Soil Monitoring 123 -- 11.2 Agricultural Robot 125 -- 11.3 Pest Control 126 -- 11.4 Precision Farming 127 -- Exercise 129 -- 12 Smart City 130 -- 12.1 Smart Transportation 131 -- 12.2 Smart Parking 132 -- 12.3 Waste Management 133 -- 12.4 Smart Grid 134 -- 12.5 Environmental Conservation 135 -- Exercise 137 -- 13 Government 138 -- 13.1 Information Technology 140 -- 13.2 Human Service 141 -- 13.3 Law Enforcement 144 -- 13.3.4 Augmenting Human Movement 147 -- 13.4 Homeland Security 147 -- 13.5 Legislation 149 -- 13.6 Ethics 152 -- 13.7 Public Perspective 155 -- Exercise 159 -- 14 Computing Platform 160 -- 14.1 Central Processing Unit 160 -- 14.1.1 System Architecture 161 -- 14.1.2 Advanced Vector Extension 164 -- 14.1.3 Math Kernel Library for Deep Neural Network 165 -- 14.2 Graphics Processing Unit 165 -- 14.2.1 Tensor Core Architecture 167 -- 14.2.2 NVLink2 Configuration 167 -- 14.2.3 High Bandwidth Memory 169 -- 14.3 Tensor Processing Unit 170 -- 14.3.1 System Architecture 170 -- 14.3.2 Brain Floating Point Format 171 -- 14.3.3 Cloud Configuration 172 -- 14.4 Neural Processing Unit 173 -- 14.4.1 System Architecture 173 -- 14.4.2 Deep Compression 174 -- 14.4.3 Dynamic Memory Allocation 174 -- 14.4.4 Edge AI Server 175 -- Exercise 176 -- Appendix A Kneron Neural Processing Unit 178 -- Appendix B Object Detection (Overview) 179 -- B.1 Kneron Environment Setup 179 -- B.2 Python Installation 180 -- B.3 Library Installation 184 -- B.4 Driver Installation 185 -- B.5 Model Installation 186 -- B.6 Image/Camera Detection 186 -- B.7 Yolo Class List 190 -- Appendix C Object Detection - Hardware 192 -- C.1 Library Setup 192 -- C.2 System Parameters 193 -- C.3 NPU Initialization 194 -- C.4 Image Detection 195 -- C.5 Camera Detection 197 -- Appendix D Hardware Transfer Mode 199 -- D.1 Serial Transfer Mode 199 -- D.2 Pipeline Transfer Mode 201 -- D.3 Parallel Transfer Mode 203 -- Appendix E Object Detection - Software (Optional) 205 -- E.1 Library Setup 205 -- E.2 Image Detection 207 -- E.3 Video Detection 208 -- Reference 211.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 12, 2022).
John Wiley and Sons
Keywords: Artificial intelligence; Intelligence artificielle; artificial intelligence; Artificial intelligence